HUBUNGAN MOTIVASI DENGAN KEGIATAN PERKULIAHAN MAHASISWA JURUSAN BIMBINGAN DAN KONSELING - Putri, Riani Eka; Ibrahim, Indra; Sukma, Dina (Universitas Negeri Padang, 2013)
Students who are motivated will prepare before attending college, in college and post-college activities. Phenomena in the field students lack motivation, see there are still students who arrive late, do not read the lecture material, playing phone while in college, and rarely repeat lecture material at home. This study revealed a motivation to lectures. Type a descriptive correlational study with findings of high student motivation, activities and lectures both significant relationship between motivation and lectures.